Pengaruh Metode Experiential Learning terhadap Kemandirian Anak Usia 4-6 Tahun - Aminah, Siti; Yuntina, Lily; Anggraeni, Rita Intan (INTELEKTIUM, 2025)
Children’s independence is a crucial aspect in supporting successful learning, yet many early childhood students still show a high level of dependence on others in carrying out daily activities. This study aims to examine the effect of the experiential learning method on children’s independence at TK Sekolah Alam Bekasi. Experiential learning emphasizes direct involvement through concrete experiences, reflection, conceptualization, and active experimentation, which are expected to enhance independence. This research employed a quantitative associative approach by distributing questionnaires to 45 respondents, and the data were analyzed using simple linear regression. The findings revealed a significant effect of experiential learning on children’s independence, with a significance value of 0.001 and an R² of 0.456, indicating that this method contributes 45.6% to the development of independence, while the remaining 54.4% is influenced by other factors. In conclusion, experiential learning is proven effective in fostering independence by improving self-confidence, responsibility, and decision-making skills.